Analysis of Economic Welfare of Village Community Using Systems Thinking Approach (A Study of Kucur Village, District of Dau, Malang Regency) - Annahar, Nasrun (Jurnal Ilmiah Administrasi Publik, 2018)
There is partial mindset among the planners and scientist about village economic welfare problems. Development programs have not achieved the goal and many studies have not been able to analyze the welfare structure of the village community comprehensively. This research using system thinking approach to seek the complexity of village community welfare problem comprehensively and completely. This research was conducted in Kucur village. A village directly adjacent to the city of Malang. The welfare system of the Kucur community consists of four subsystems, namely: skill, education level, business turnover and health level. The sensitivity test shows that the elements that most influence the welfare system of village communitiy of Kucur in sequence are: loan, transportation access, savings, communications access, spacious house, pets and business turnover.